Pengembangan TiO2 nanowire terdoping Nikel Kobalt sebagai Fotokatalis yang Efisien untuk Menghilangkan Pewarna Tartrazine - Misriyani; If'all; Lutfiah Sahabuddin (Jurnal Penelitian Pendidikan IPA, 2024)
Tartrazine is a yellow synthetic dye that is widely used as a coloring agent in food and beverage products. However, the safety of this chemical compound is still a concern due to potential health risks such as allergic reactions, hyperactive behavior in children, increased risk of cancer and other negative impacts. This research aim to introduces a new approach to reduce the concentration of tartrazine dye using cobalt and nickel doped TiO2 nanowires. Cobalt- and nickel-doped TiO2 nanowires were synthesized by a hydrothermal method, followed by thermal treatment at 270°C, and then used in a photocatalytic reactor using UV irradiation to facilitate the reduction of tartrazine concentration. Material characterization was carried out to determine the morphology and crystallinity of the photocatalyst which is effective in reducing the absorption of tartrazine solution. The photocatalytic degradation experiment demonstrates the ability of the synthesized material as a photocatalyst, effectively reducing the absorbance of tartrazine solution, a commonly used food coloring. This finding promises significant progress in the development of sustainable food safety strategies by offering a dye degradation method.